2017
DOI: 10.1016/j.ecoenv.2017.07.057
|View full text |Cite
|
Sign up to set email alerts
|

Sub-lethal effects of essential oil of Lippia sidoides on drywood termite Cryptotermes brevis (Blattodea: Termitoidea)

Abstract: The drywood termite Cryptotermes brevis (Walker, 1853) (Kalotermitidae) is one of the most important wood structural pest in the world. Substances from the secondary metabolism of plants (e.g., essential oils) have been considered an environmentally safer form of control for urban pests, such as termites. In the present study, we analyzed the lethal and sub-lethal effects of essential oil of Lippia sidoides and its major components on C. brevis pseudergates in two routes of exposure (contact and fumigation). T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
24
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(24 citation statements)
references
References 33 publications
0
24
0
Order By: Relevance
“…The authors found that Pogostemon cablin EO was the most effective (LC 50 ) at 0.32 μl/ ml and 0.29 μl/ ml, concentrations lower than those observed here (Bacci et al,2015), while L. sidoides was less effective, with a median effect on the termites tested at 2.41 and 3.47 μl/ ml, respectively. The insecticidal activity of L sidoides against Cryptotermes brevis (Walker, 1853) (Kalotermitidae) has also been reported using the fumigation test, with CL 50 estimated at 9.10 and 23.6 μL/ L of beans (Santos et al, 2017). It is important to note that individual characteristics such as cuticle thickness, associated with different application methods, can influence inter or intragroup tolerance and resistance (Haddi et al, 2015;Pinto-Zevallos & Zarbin, 2013).…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…The authors found that Pogostemon cablin EO was the most effective (LC 50 ) at 0.32 μl/ ml and 0.29 μl/ ml, concentrations lower than those observed here (Bacci et al,2015), while L. sidoides was less effective, with a median effect on the termites tested at 2.41 and 3.47 μl/ ml, respectively. The insecticidal activity of L sidoides against Cryptotermes brevis (Walker, 1853) (Kalotermitidae) has also been reported using the fumigation test, with CL 50 estimated at 9.10 and 23.6 μL/ L of beans (Santos et al, 2017). It is important to note that individual characteristics such as cuticle thickness, associated with different application methods, can influence inter or intragroup tolerance and resistance (Haddi et al, 2015;Pinto-Zevallos & Zarbin, 2013).…”
Section: Discussionmentioning
confidence: 94%
“…The insecticidal efficiency of this genus has been reported for the species Lippia gracilis and Lippia sidoides against Sitophilus zeamais (Castro Coitinho et al, 2006), Aedes aegypti and Culex quinquefasciatus (Costa et al, 2005), respectively. Although these studies reinforce the insecticidal properties of Lippia species against other classes of arthropods, research on the insecticidal potential of other representatives of this genus remains scarce, particularly against termites (Evans & Iqbal, 2015;Santos et al, 2017). Thus, the present study aimed to investigate the chemical composition and insecticidal potential of essential oils of the species Lippia lasiocalycina, Lippia insignis and Lippia thymoides to control Nasutitermes corniger Motsch (Isoptera: Termitidae).…”
Section: Introductionmentioning
confidence: 92%
“…The individual behaviour bioassays indicated that treated ants do not notice self‐contamination since no self‐grooming increase has been observed, a common behaviour in social insects when they detect the presence of contaminating agents in their integuments (Galvanho et al., ; Santos et al., ).…”
Section: Discussionmentioning
confidence: 99%
“…and patchouli ( Pogostemon cablin [Blanco] Benth.) reduced the collective interactions and walking abilities of various termites ( Bacci et al, 2015 ; Santos et al, 2017 ). Adding these essential oils on the broken mud tubes may interfere with the escaping behaviors of O. formosanus .…”
Section: Discussionmentioning
confidence: 99%